Tectonic controls on the salt diapir-related Mississippi Valley-type lead-zinc mineralization of Fej El Adoum ore deposit (Northern Tunisian Atlas): Constrains from detailed gravity and drill hole data. (September 2021) - Barhoumi, Anis; Belkhiria, Wajdi; Ayari, Jamel; Hatira, Nouri; Braham, Ahmed; Dhaha, Faouzi
Abstract: Relationship between salt domes and base metal mineralization is widely recognized across many salt-bearing basins (e.g., US Gulf Coast, Southern Europe and North Africa). In the northern Tunisian Atlas, the Mississippi Valley-type Fej El Adoum lead-zinc deposit represents one of these salt-related ore deposits. It consists of a combination of stratabound, veins, stockworks and cavity filling ore bodies, hosted by dolostone and limestone units, formed along the transition between Triassic evaporites and Cretaceous limestone. In the aim to better understand the concealed complex geological structures across the area, new-acquired detailed gravity data, constrained with field investigation and drill hole data were analyzed. Particularly, edge source detection techniques such as vertical gradient, total horizontal gradient and theta angle map were applied to outline structural contacts related to subsurface density variations. The main detected lineaments are in N–S, E-W and NW-SE directions. The N–S direction represents the deepest and most important lineament in direct contact with the evaporitic Triassic, while the transverse E-W direction is related to dextral strike-slip faults that subdivide the area into blocks. These major deeper lineaments have controlled the growth of the Triassic salt dome mainly during the Albo-Aptian as revealed by pinch outs of these series in direction of the crest of the structure. The detected lineaments seem to play a significant role in: (1) providing favorable pathways for the migration and ascent of mineralized fluids and (2) creating open space filling mainly at the interferences of N–S and E-W trending faults present at the contact between Triassic evaporitic unit and Cretaceous limestone. Our results suggest further reserves mainly in the E-W Ain Said occurrence and West of the Dar N'Hal closed mine. Our study also revealed the importance of structural study in the understanding of complex structures such as highly deformed salt dome cap rocks such as the Fej El Adoum diapiric structure. Graphical abstract: Image 1 Highlights: Tectonic control on Pb–Zn deposits is studied in Fej El Adoum (northern Tunisian). Deep-seated faults controlled the Triassic salt dome growth in Fej El Adoum. Intersection of N–S and E-W trending faults in salt cap rocks provided open space for ore to deposit. Cap-rock atop salt and overturned diapir models are characterized in Fej El Adoum.